Chemical, antioxidant, functional and thermal properties of rice bran proteins after yeast and natural fermentations - Chinma, Chiemela Enyinnaya; Ilowefah, Muna; Shammugasamy, Balakrishnan; Ramakrishnan, Yogeshini; Syed Muhammad, Sharifah Kharidah (Institute of Food Science and Technology, 2014)
The paper focuses on the chemical, antioxidant, functional and thermal properties of rice bran proteins after yeast, natural fermentations and unfermented rice bran. Protein content of yeast-fermented rice bran protein concentrate (YFRBPC), naturally fermented rice bran protein concentrate (NFRBPC) and unfermented rice protein concentrate (UFRBPC) were 72.50%, 68.92% and 65.73%, respectively, while ash content were 4.72%, 4.61% and 3.04%, respectively. The total amino acids of YFRBPC, NFRBPC and UFRBPC were 123.16, 118.45 and 99.39, respectively. DPPH radical inhibition of YFRBPC, NFRBPC and UFRBPC were 58.62%, 55.29% and 47.14%, respectively, while ferric reducing ability power were 0.73, 0.58 and 0.41 mmol TE per gram, respectively. The highest foam capacity of UFRBPC (57.56%), NFRBPC (64.15%) and YFRBPC (76.00%) was observed at pH 9.0. YFRBPC and NFRBPC were lighter in colour than UFRBPC. YFRBPC had higher denaturation temperature and enthalpy value than NFRBPC and UFRBPC. The β-sheets structures were more in YFRBPC and NFRBPC than UNFBPC.